HealthyEnv: a tool to assist in health assessment of software repositories - Winter, Diego; Avelino, Guilherme; Miranda, Charles (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2022: Anais do XXXVI Simpósio Brasileiro de Engenharia de Software, 2022)
Most of the software developed today, whether proprietary or open source, has as its base infrastructure for its construction software components developed by open source communities. In this context, the concern with the quality, reliability and maintainability of such software components is of great importance. To evaluate and monitor software and its development community, tools are needed to assist in the process. Thus, in this work we present a tool, called HealthyEnv, which helps in the evaluation of the health of software projects, providing not only a series of metrics automatically computed from the software repository, but also reference values to assist in the interpretation of results.